Channel Equalization and Phase Noise Compensation Free DAPSK-OFDM Transmission for Coherent PON System - Kyoung-Hak Mun; Sang-Min Jung; Soo-Min Kang; Sang-Kook Han (IEEE Photonics Journal)
Channel equalization and phase noise compensation are required in coherent optical orthogonal frequency-division multiplexing (CO-OFDM) transmission systems for reliable performance. In general, redundant data such as training symbols and pilot tones are necessary for channel and phase noise estimation in quadrature amplitude modulation (QAM) based CO-OFDM systems, which reduces the spectral efficiency of the system. Especially, in the coherent passive optical network (PON), the redundancy increases as the number of subscribers increases. In this letter, we propose a differential amplitude shift keying (DAPSK)-based CO-OFDM transmission for PON system, which does not require channel equalization and phase noise compensation processes. The proposed DAPSK-based CO-OFDM transmission was experimentally demonstrated, and the performance according to receiver launched power and the number of subcarriers was compared with QAM-based CO-OFDM.